Hubungan Pengetahuan dan Sikap dengan Perilaku Konsumsi Gula, Garam, dan Lemak Pada Siswa Sekolah Menengah Pertama - Safira Andjani; Siti Rahayu Nadhiroh (Media Gizi Kesmas, 2025)
Background: Junior High School (JHS) students are teenagers who are vulnerable to having health problems with the occurrence of problems in their nutritional status. One of the causes of abnormal nutritional status is through eating patterns such as excessive consumption of food with additional food ingredients such as sugar, salt, and fat (oil). Recommendations for consuming these additional ingredients have been written in Ministerial Regulation of the Ministry of Health No. 30 of 2013. Objectives: The purpose of this study was to analyze the association between knowledge and attitudes with practices about sugar, salt, and fat consumption of students at State Junior High School 17 Surabaya. Methods: This study is included in quantitative research with a cross-sectional research design. The sample used was 82 students. Data collection included anthropometric measurements and filling out questionnaires regarding sugar, salt, and fat. Data were analyzed using the chi-square test. Results: The results showed that there was an association between knowledge and practices regarding sugar, salt, and fat consumption (p=0.000) as well as attitudes and practices regarding sugar, salt, and fat consumption (p=0.000). Conclusion: The conclusion of this study is that knowledge and attitudes are related to practices regarding sugar, salt, and fat consumption, and practices about sugar, salt, and fat consumption have a relationship with the nutritional status of students. Suggestions that can be given are that schools can evaluate school canteens related to food and drinks with high sugar, salt, and fat content to reduce the chances of students having poor consumption behavior, and students are expected to always increase their insight and be careful in consuming food and drinks that contain additional food ingredients.